PENDUGAAN EROSI TANAH PADA BERBAGAI PENGGUNAAN LAHAN DAN KEMIRINGAN LERENG DI KECAMATAN WONOSALAM, KABUPATEN JOMBANG - Charismanda, Muhammad Luthfi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2024)
Indonesia is a tropical country prone to land degradation, with erosion being one of the main causes. The damage and loss of hydrological and economic functions are consequences of erosion. Wonosalam Subdistrict, Jombang Regency, is an area located at the foot of Mt. Anjasmoro, ranging in elevation from 600 to 1200 meters above sea level (masl). Wonosalam Subdistrict excels in the plantation sector, particularly in Jombang Regency. The area's characteristics, marked by steep slopes and numerous dragon's back ridges, make it highly susceptible to erosion. Consequently, if land management does not adhere to soil and water conservation principles, a decline in soil function will adversely impact the key sector of plantations. This study employed a descriptive-exploratory method through field surveys and purposive sampling. Samples were taken at various slope levels, including gentle slopes (8-15%), moderately steep slopes (16-25%), and steep slopes (26-40%), across forest, plantation, dryland cultivation, and paddy fields. Erosion estimation utilized the Universal Soil Loss Equation (USLE) proposed by Wichsmeier and Smith (1978). The research findings indicate that the Land Unit with the highest actual erosion value is dryland cultivation with a slope of 25-40% or T1K3, with a value of 1238.44 tons/ha/year. In contrast, the lowest is Paddy Field 3 with a slope of 8-15% or Sw1K3 with a value of 0.16 tons/ha/year. Conservation guidelines are determined based on the Erosion Index (EI), prioritizing the scale to identify the lands that require immediate restoration. All dryland fall under Priority I in the conservation plan. Conservation directives involve both vegetative and mechanical methods, such as constructing bench terraces and planting crops suitable for the socio-economic conditions of the Wonosalam Subdistrict, such as coffee or durian.